Expression and function of EZH2 in synovial fibroblasts: epigenetic repression of the Wnt inhibitor SFRP1 in rheumatoid arthritis. Issue 8 (22nd April 2011) - Trenkmann, Michelle; Brock, Matthias; Gay, Renate E; Kolling, Christoph; Speich, Rudolf; Michel, Beat A; Gay, Steffen; Huber, Lars C
Abstract : Objectives: To study the expression, regulation and function of the histone methyltransferase enhancer of zeste homologue 2 (EZH2) in synovial fibroblasts (SF) from patients with rheumatoid arthritis (RA) and osteoarthritis (OA). Methods: SF were obtained from RA and OA patients undergoing joint surgery. Expression levels were assessed by quantitative real-time PCR and western blot. Kinase inhibitors and reporter gene assays were employed to study signalling pathways. Functional analyses included EZH2 overexpression by plasmid transfection and gene silencing by small interfering RNA. Chromatin immunoprecipitation assay was used to analyse histone methylation within distinct promoter regions. Results: By studying the expression and function of EZH2 in SF the authors found that EZH2 is overexpressed in rheumatoid arthritis synovial fibroblasts (RASF) and further induced by tumour necrosis factor alpha through the nuclear factor kappa B and Jun kinase pathways. As a target gene of EZH2 the authors identified secreted frizzled-related protein 1 (SFRP1), an inhibitor of Wnt signalling, which is associated with the activation of RASF, and show that SFRP1 expression correlates with the occupation of its promoter with activating and silencing histone marks. Conclusions: These data strongly suggest that the chronic inflammatory environment of the RA joint induces EZH2 and thus might cause changes in the epigenetic programmes of SF.